Exploring STEM Learning in Lower Grade of Primary Education - Riastini, Putu Nanci; I Nengah Suparta; Luh Putu Sri Lestari; Ade Dwi Utami (Exploration in Early Childhood Research, 2024)
Studying STEM is essential for students, even the lower grades of elementary school, to develop 21st century skills from a young age. Unfortunately, research regarding teaching STEM to younger students and professional training models for educators to integrate STEM in elementary schools is lacking. This research aims to determine the application of STEM in lower elementary grades; examine the factors that influence the effectiveness of STEM implementation in lower elementary grades; investigate strategies used to introduce STEM in lower elementary grades; and assessing STEM evaluation methods to increase the effectiveness of STEM implementation in the lower elementary grades. The initial phase of the project will involve conducting exploratory research on STEM in elementary school classrooms. This research will use a combination of approaches, starting with quantitative research and continuing with qualitative research. Surveys will be used for quantitative data collection, while interviews, focus group discussions, and observations will be used for qualitative data collection. Quantitative data analysis will involve descriptive and inferential statistics. Qualitative data analysis will involve content analysis followed by the application of triangulation. The research results show that STEM is very necessary to improve elementary school students' thinking, STEM can be combined with games to attract students' attention. A simple example of applying STEM is a simple project, so it can train students to work in groups which will have an impact on their social emotional abilities. The results of this research can be used as a reference for future STEM applications.